QTL for induced resistance against leaf rust in barley - Matros, Andrea; Schikora, Adam; Ordon, Frank; Wehner, Gwendolin (Frontiers in Plant Science, 2023)
Leaf rust caused by Puccinia hordei is one of the major diseases of barley (Hordeum vulgare L.) leading to yield losses up to 60%. Even though, resistance genes Rph1 to Rph28 are known, most of these are already overcome. In this context, priming may promote enhanced resistance to P. hordei. Several bacterial communities such as the soil bacterium Ensifer (syn. Sinorhizobium) meliloti are reported to induce resistance by priming. During quorum sensing in populations of Gram-negative bacteria, they produce N-acyl homoserine-lactones (AHL), which induce resistance in plants in a species- and genotype-specific manner. Therefore, the present study aims to detect genotypic differences in the response of barley to AHL, followed by the identification of genomic regions involved in priming efficiency of barley. A diverse set of 198 spring barley accessions was treated with a repaired E. meliloti natural mutant strain expR+ch producing a substantial amount of AHL and a transformed E. meliloti strain carrying the lactonase gene attM from Agrobacterium tumefaciens. For P. hordei resistance the diseased leaf area and the infection type were scored 12 dpi (days post-inoculation), and the corresponding relative infection and priming efficiency were calculated. Results revealed significant effects (p<0.001) of the bacterial treatment indicating a positive effect of priming on resistance to P. hordei. In a genome‐wide association study (GWAS), based on the observed phenotypic differences and 493,846 filtered SNPs derived from the Illumina 9k iSelect chip, genotyping by sequencing (GBS), and exome capture data, 11 quantitative trait loci (QTL) were identified with a hot spot on the short arm of the barley chromosome 6H, associated to improved resistance to P. hordei after priming with E. meliloti expR+ch. Genes in these QTL regions represent promising candidates for future research on the mechanisms of plant-microbe interactions.